Axioms for Lexicographic Preferences - Fishburn, Peter C. (Review of Economic Studies, 1975)
Journal Article Axioms for Lexicographic Preferences Get access Peter C. Fishburn Peter C. Fishburn Pennsylvania State University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 3, July 1975, Pages 415–419, https://doi.org/10.2307/2296854 Published: 01 July 1975